A novel multicomponent microwave-assisted synthesis of 5-aza-adenines - Dolzhenko, Anton; Kalinina, S.; Kalinin, D. (Royal Society of Chemistry, 2013)
A novel multicomponent strategy for the efficient synthesis of 5-aza-adenines was developed. 5-Azaadenines were prepared in a one-pot fashion from 5-amino-1,2,4-triazoles, cyanamide and triethylorthoformate under microwave irradiation. The operational simplicity, efficiency and accessibility of thismethod make it highly attractive for the generation of bioactive compound libraries